2020
DOI: 10.1115/1.4048814
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Design Fixation: A Visualization Tool for Enhancing Situation Awareness

Abstract: External stimuli can stimulate a designer's creativity and improve the outcome of design ideation for product/service concept generation. A psychological phenomenon that may occur during such utilization of external stimuli is design fixation, which is widely believed to adversely affect the ideation outcome. One of the difficulties in preventing or alleviating design fixation is that the designer may not easily detect or predict its occurrence during the mentally demanding task of ideation. In an effort to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Fixation metrics are correlated with SA in many studies [21][22][23]. Several studies [24,25] have also confirmed moderate correlations between saccade metrics and SA.…”
Section: Introductionmentioning
confidence: 83%
“…Fixation metrics are correlated with SA in many studies [21][22][23]. Several studies [24,25] have also confirmed moderate correlations between saccade metrics and SA.…”
Section: Introductionmentioning
confidence: 83%
“…In some cases, fixation is due to the stimuli themselves (Hay et al ., 2020) or to the repeated use of only a small portion of the external stimuli available (Hwang et al ., 2021). For example, visual stimuli, such as images of everyday life scenes or line drawings and photographs, can both guide the designer to inappropriately repeat some features of the stimuli in their final ideas (respectively, Purcell and Gero, 1992; Hernandez et al ., 2010).…”
Section: Results From the Reviewmentioning
confidence: 99%
“…New methods have been developed in the literature to help novice designers recognize and avoid the fixation phenomenon. Hwang et al (2021) developed a support system that keeps track of designers' use of the available external stimuli and guides individuals in redistributing their attention to unused stimuli. Design by analogy can help reduce design fixation by supporting designers in constructing distant analogies from the design problem domain while still relying on prior knowledge, experience, or external stimuli (Moreno et al, 2016).…”
Section: Metrics For Performance Evaluation and The Problem Of Fixationmentioning
confidence: 99%
“…Design fixation, a complex phenomenon, can be caused by many factors. As workload increases, designers always find ways of working faster to meet time constraints and may end up in daily routines, leading to design fixation (Hwang et al, 2021). The qualities of a good idea include originality, appropriateness, and the surprisingness of an idea.…”
Section: Literature Surveymentioning
confidence: 99%